A Farm Boy’s Memory of the Cavalry - John McCormally (Symphony in the Flint Hills, 2013)
“They’re ghost riders now, those Fort Riley Cavalrymen.“ So wrote John McCormally in the Salina Journal, reprinted in the Daily Union Centennial Edition, June 24, 1953.
Keywords: cavalry; memory; story; army; Ft. Riley; military; troops; soldiers; farm boy; farmer; US Cavalry; Custer; Comanche; Little Big Horn; history; tradition; honor; cowboy; saddles; description; peacetime; war; golden years